Middle atmosphere dynamical sources of the semiannual oscillation in the thermosphere and ionosphere. Issue 1 (5th January 2017) - Jones, M.; Emmert, J. T.; Drob, D. P.; Siskind, D. E.
Abstract: The strong global semiannual oscillation (SAO) in thermospheric density has been observed for five decades, but definitive knowledge of its source has been elusive. We use the National Center of Atmospheric Research thermosphere‐ionosphere‐mesosphere electrodynamics general circulation model (TIME‐GCM) to study how middle atmospheric dynamics generate the SAO in the thermosphere‐ionosphere (T‐I). The "standard" TIME‐GCM simulates, from first principles, SAOs in thermospheric mass density and ionospheric total electron content that agree well with observed climatological variations. Diagnosis of the globally averaged continuity equation for atomic oxygen ([O]) shows that the T‐I SAO originates in the upper mesosphere, where an SAO in [O] is forced by nonlinear, resolved‐scale variations in the advective, net tidal, and diffusive transport of O. Contrary to earlier hypotheses, TIME‐GCM simulations demonstrate that intra‐annually varying eddy diffusion by breaking gravity waves may not be the primary driver of the T‐I SAO: A pronounced SAO is produced without parameterized gravity waves. Key Points: The TIME‐GCM simulates a realistic semiannual oscillation (SAO) in the thermosphere and ionosphere (T‐I) from first principles Resolved‐scale variations in oxygen transport in the upper mesosphere drive the T‐I SAO simulated by TIME‐GCM Model runs indicate that intra‐annually varying eddy diffusion is not the primary driver of the T‐I SAO